Sovereign debt issuance and selective default - Wojtek Paczos; Kirill Shakhnov (Cardiff University, Cardiff Business School, 2024)
Sovereigns issue debt on both domestic and foreign markets and the two debts are uncorrelated in the data. Sovereigns default mostly selectively. We propose a theory to rationalize these observations. A government chooses the optimal combination of two debts to smooth consumption, which is subject to output shock and volatile tax distortions. In equilibrium, it mostly relies on domestic debt to smooth the tax wedge and on foreign debt to smooth the output shock. Issuing either debt is less costly than raising taxes, but it is subject to default risk due to the government's limited commitment. A quantitative, calibrated model with two shocks and two debts replicates well debt-to-GDP ratios, default frequencies, cyclical properties of emerging economies and behavior of aggregates around default episodes.
Keywords: F34; G15; H63; 330; sovereign debt; selective default; debt composition